VALIDASI METODE ANALISA PENETAPAN KADAR EPIGALOKATEKIN GALAT DENGAN KROMATOGRAFI CAIR KINERJA TINGGI - Nining Sugihartini; Achmad Fudholi; Suwidjiyo Pramono; Sismindari Sismindari (Pharmaciana, 2014)
High Performance Liquid Chromatography (HPLC) was one of analytical methods commonlyto determine the concentration of epigallocatechin gallate (EGCG) on green tea extract. The methodmust be validated in order to fit to its purpose. The aim of this research was to prove that the usedmethod has selectifity, liniearity, precise, accurate and know limit of detection (LOD) and limit ofquantification (LOQ) is acceptable. The selectifity of analytical method was determined bycalculating the resolution value between two peak. Data from 10 ug/ml and 100 ug/ml with 5replicates would give precition and accuration. Precition was known from CV value and accurationwas known from recovery value in each concentration. Liniearity was known from regression linearbetween concentration and wide area of peak. From regresion linear could calculate LOD and LOQ.Research show that method of analyse have selectificity with Rs= 2,27>1,5; liniearity with r= 0,99;precision with CV 8,74% at concentration 200 µg/ml and 3,74% at concentration 500 µg/ml;accuration with recovery 99,76% at concentration 200 µg/ml and 100,52% at concentration 500 µg/mland the value of LOD is 33,28 ug/ml and LOQ is 110,93 ug/ml.